Myo-inositol: micronutrient for "fine tuning" of the female reproductive sphere - I.Yu. Torshin; O.A. Gromova; A.G. Kalacheva; V.I. Demidov (LCC «Medicine-Inform», 2018)
Myo-inositol: micronutrient for "fine tuning" of the female reproductive sphere I.Yu. Torshin1, O.A. Gromova1, A.G. Kalacheva2, N.K. Tetruashvili3, V.I. Demidov2 1 Federal Research Center "Computer Science and Control" of the Russian Academy   of Sciences, Moscow, Russian Federation 2 Ivanovo State Medical Academy, Ivanovo, Russian Federation 3 V.I. Kulakov Research Center of Obstetrics, Gynecology and Perinatology, Moscow,   Russian Federation Myo-inositol is necessary for the synthesis of signal molecules of inositol phosphates involved in effect mediation of reproductive hormones. Insufficiency of myo-inositol is associated with menstrual irregularities, infertility, polycystic ovaries and congenital malformations of the fetus. Myo-inositol supplement improves the formation of ovulatory cycles, mature oocytes, the probability of pregnancy; reduce the risk of folate-resistant malformations, gestational diabetes, and fetal macrosomia. Myo-inositol favorably affects the lipid profile of the blood; prevents excessive weight gain during pregnancy, counteracts the formation of glucose tolerance and insulin resistance in women with menstrual irregularities, reduces chronic inflammation in the atherogenic profile of the blood. Myo-inositol supports antitumor immunity. The level of myo-inositol in the body decreases with the use of nephrotoxic medicinal products. Myo-inositol dependence increases with kidney pathology (pyelonephritis, glomerulonephritis, diabetic nephropathy, nephropathy of pregnancy, renal form of hypertension, etc.), with hyperglycaemic type of nutrition. Key words: myo-inositol, ovulation, hormonal receptors, polycystic ovary, folate-resistant developmental defects, Miofert. For citation: Torshin I.Yu., Gromova O.A., Kalacheva A.G. et al. Myo-inositol: micronutrient for "fine tuning" of the female reproductive sphere. Russian Journal of Woman and Child Health. 2018;1(2):148-155.